Problems and prospects for the strategic development of the world energy system - SANDU Maxim (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
in the presented article modern challenges, problems and prospects for strategic development of global energy system are described. The presence of some energy problems serves as starting points for improvement and emergence of trends associated primarily with technological innovations in extraction, transportation and supply of energy resources. At the moment the global energy picture of the world clearly demonstrates the general trends in the development of globalization processes. Results of research of policies and strategies of provision of energy security of regions of the world demonstrate the importance of context of international collaboration for effective development in a single vector.